Pseudovaluations on WFI Algebras - Young Bae Jun; Min Su Kang; Eun Hwan Roh (International Journal of Mathematics and Mathematical Sciences)
Using Buşneag's model, the notion of pseudovaluations (valuations) on a WFI algebra is introduced, and a pseudometric is induced by a pseudovaluation on WFI algebras. Given a valuation with additional condition, we show that the binary operation in WFI algebras is uniformly continuous.